Meta Analisis Pengaruh Problem Based Learning Terhadap Keterampilan Berpikir Kritis Di Sekolah Dasar - Dwi Ajeng Febrina; Gamaliel Septian Airlanda (Peneliti.net, 2020)
The purpose of this study was to analyze previous studies published in publications so as to obtain a study based on Problem Based Learning on critical thinking skills in mathematics lessons in elementary schools. Not only is the theory given or memorized, but students are able to solve problems that occur in learning so that learning outcomes become optimal and think critically and logically (Hallatu, 2017). In general, it means that mathematics is an exact science equipped with reasoning. In this study, using this type of experimental research with meta-analysis techniques. The steps include: (1) determining and studying the research topic; (2) searching and collecting several sources on a particular topic; (3) calculating how big the impact will be with a certain model; (4) attract attention and interpret research results. The results of this study indicate that the Problem Based Learning learning model is sufficient to improve students' critical thinking skills in elementary schools. This can be seen from the effect size value of 0.39 with a low category.